2020
DOI: 10.1038/s41598-020-60295-w
|View full text |Cite
|
Sign up to set email alerts
|

Anticandidal and In vitro Anti-Proliferative Activity of Sonochemically synthesized Indium Tin Oxide Nanoparticles

Abstract: The present work demonstrates the synthesis, characterization and biological activities of different concentrations of tin doped indium oxide nanoparticles (Sn doped in 2 o 3 nps), i.e., (Sn/in = 5%, 10% and 15%). We have synthesized different size (38.11 nm, 18.46 nm and 10.21 nm) of Sn doped In 2 o 3 nps. by using an ultra-sonication process. the Sn doped in 2 o 3 nps were characterized by by x-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) which confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 33 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…The study of morphogenesis using SEM showed that MOS extract affects the cell wall at the initial stage, and later penetrates and accumulates at the surface membrane. This leads to an interruption in the metabolic activities of bacterial cells and initiates cell death [ 30 ]. The present study illustrates that the MOS extract causes damage to the microbial cell surface, thereby causing significant antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of morphogenesis using SEM showed that MOS extract affects the cell wall at the initial stage, and later penetrates and accumulates at the surface membrane. This leads to an interruption in the metabolic activities of bacterial cells and initiates cell death [ 30 ]. The present study illustrates that the MOS extract causes damage to the microbial cell surface, thereby causing significant antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…First, cells were cultured in 96 well-plates according to the earlier specified method. Dulbecco’s modified Eagle’s medium (DMEM), supplemented with other reagents (selenium chloride, fetal bovine serum, L-glutamine and antibiotics), was added to the plates for cell growth [ 29 , 30 ].…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…9 The most comprehensively studied particles having superior antimicrobial activity includes silver, gold, zinc oxide, copper, copper oxide, titanium dioxide and iron oxide NPs. [10][11][12][13] Spinel ferrite (SF) are ferromagnetic compounds that are usually oxides of various transition metals, containing iron e.g. ZnFe 2 O 4 , NiFe 2 O 4 , Zn/NiFe 2 O 4 , CoFe 2 O 4 , MnFe 2 O 4 , and MgFe 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…ZnFe 2 O 4 , NiFe 2 O 4 , Zn/NiFe 2 O 4 , CoFe 2 O 4 , MnFe 2 O 4 , and MgFe 2 O 4 . [13][14][15] These NPs have unique optical, electrical and magnetic properties and can easily be magnetized or demagnetized due to their so and insulating nature. SF NPs are mostly used as magnetic, refractory and catalytic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive fungal infections are continuing to increase as a result of the increase of immunosuppressed individuals, the wide use of antibacterial agents, and the rapid development of invasive operation technology (Marks et al, 2017). Candida species are the third most common opportunistic fungal pathogens (Wisplinghoff et al, 2004;Rehman et al, 2020), and Candida albicans, the most commonly reported fungi, can cause bloodstream infections with a high mortality ranging between 40 and 60% (Choudhury, 2018;Brunetti et al, 2019;Poissy et al, 2020). There is a paucity of therapeutic options of antifungal agents for fungal pathogens.…”
Section: Introductionmentioning
confidence: 99%